Influencia de los factores climáticos en la producción del cultivo de ajonjolí (Sesamum indicum) - Medrano Zumba, Andrea Belén (2024)
This document addressed the topic of the influence of climatic factors on the production of sesame (Sesamum indicum) crops. This food is very versatile, providing great benefits that are very important worldwide due to its nutritional value as a source of nutrients, healthy fats, fiber, vitamins and minerals. The main objective was to determine the climatic effects on the production of sesame crops. An investigative methodology was proposed with a qualitative approach and a descriptive scope. In addition, to prepare this document, information was searched in scientific articles, websites and virtual libraries. The results obtained on the climatic factors that influence the production of sesame crops indicated that these factors can have an impact on economic losses for farmers, among the main ones are droughts, frosts, excessive rains and strong winds. Droughts can reduce the supply of water available to plants, which can affect their growth and development by producing small seeds. The sesame crop is extremely sensitive to frost and cannot tolerate sub-zero temperatures. It was concluded that the climatic factors that influence the production of sesame crops affect the production of seeds in texture, flavor and appearance of the final production of the crop, giving significantly poor profitability and sustainability, causing economic and income losses to producers. For this reason, farmers must take measures to mitigate the effects of these climatic factors and reduce the risk of economic losses in the crop.